Significance of Rate-Pressure Product and Duke Treadmill Score in Predicting Disease Severity in Patients with Coronary Artery Disease: A Cross-sectional Study - EV Shaveen; K Jayaprakash; V Sudhakumary; Suresh Madhavan; Cicy Bastian; VL Jayaprakash (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Exercise electrocardiography is a well-established and cost-effective investigation for evaluating Coronary Artery Disease (CAD). The Rate-pressure Product (RPP), which is the product of maximal Systolic Blood Pressure (SBP) and peak Heart Rate (HR) during exercise, is a widely accepted parameter reflecting cardiac work and evaluating ventricular function. The use of Duke Treadmill Score (DTS) improves the diagnostic accuracy of exercise-induced ST-segment depression and has been observed to provide independent prognostic information. It has been shown that DTS provides information about the complexity of coronary artery lesions assessed by invasive coronary artery testing. Aim: To determine the significance of RPP and DTS in predicting the severity and complexity of angiographic lesions in patients with Stable Ischemic Heart Disease (SIHD) and a positive Treadmill Test (TMT). Materials and Methods: This study involved 100 consecutive patients with a positive TMT but no prior history of Acute Coronary Syndrome (ACS) who underwent coronary angiography at Government Medical College, Kottayam, Kerala, India, between March 2018 and March 2019 after obtaining ethical clearance from the Institutional Review Board. The DTS and RPP were calculated for these patients. All patients then underwent coronary angiography, and their SYNTAX scores were calculated. Correlation analysis was performed to assess the relationship between DTS, RPP, and SYNTAX score using Spearman's correlation coefficient. The Kruskall-Wallis test was used to compare risk factors among groups. Results: A total of 100 patients were evaluated, ranging in age from 40 to 74 years with an average age of 57 years. The average SYNTAX score was 15, ranging from 2 to 56. The average Duke TMT score was -5.2, ranging from 6 to -22. There was a significant negative correlation between DTS and angiographic severity determined by SYNTAX score (r=-0.702, p=0.001). The average RPP was 22174, ranging from 14000 to 37620. The study showed a significant negative correlation between RPP and SYNTAX score (r=-0.201, p=0.04). Diabetic patients had a significantly higher SYNTAX score compared to non-diabetics (r=-0.602, p=0.013). Additionally, a significant negative correlation was observed between the Metabolic Equivalents (METs) attained, duration of exercise, and the SYNTAX score. Conclusion: DTS and RPP derived from the exercise treadmill test have a significant negative correlation with the severity and complexity of CAD as determined by the SYNTAX score in coronary angiography.